Molecular and pathological profiling of corresponding treatment-naïve and neoadjuvant pazopanib-treated high-risk soft tissue sarcoma samples of the GISG-04/NOPASS study - Gaiser, Timo; Sauer, Christian; Marx, Alexander; Jakob, Jens; Kasper, Bernd; Hohenberger, Peter; Hirsch, Daniela; Ronellenfitsch, Ulrich (Biology, 2021)
BRAF V600E; CDK4; MAP2K1 E203K; NGS; STS; next generation sequencing; pazopanib; soft tissue sarcoma